Comparison of wood harvesting methods in the Republic of Karelia - Syunev, Vladimir; Sokolov, Anton; Konovalov, Alexandr; Katarov, Vasily; Seliverstov, Alexandr; Gerasimov, Yuri; Karvinen, Sari; Välkky, Elina (Finnish Forest Research Institute, 2009)
Impacts of cut-to-length, tree-length and full-tree harvesting technology on direct operating costs, productivity, forest environment, ergonomics and work safety, as well as on wood quality were studied in 2007 and 2008 in 15 harvesting companies in the Republic of Karelia, Russia. Productivity varied within a relatively wide range from 20 to 150 m